A study on the factors influence public preference towards Takaful / Yusniza Abdulah - Abdulah, Yusniza (2015)
This research is conducted in purpose to determine the most influence factors that affect the public preferences towards Takaful. There are three variables that have been determined as the influenced factors based on the studies that have been done before. The three independent variables are products and services of Takaful, public religious adherence and also Takaful advertisements whereby the dependents variables is public preference towards Takaful. The research on Takaful have been chosen because of the highly demand of the Islamic products and services recently. The researcher targeted 100 respondents from the area of Selangor, Kuala Lumpur and Melaka. Approximately of 100 questionnaires have been distributed and collected back by hand and the result and data have been recorded. The result and data of the findings have been analyzed by using the SPSS software. From the result, it can be conclude that there are significant relationships between the independents variables with the dependent variables. Besides that, the independent variables also give influence to the dependent variables. As for the conclusions, the researcher has suggested some recommendations for this study.